Non-invasive vagus nerve stimulation (nVNS) for the preventive treatment of episodic migraine: The multicentre, double-blind, randomised, sham-controlled PREMIUM trial. (October 2019) - Diener, Hans-Christoph; Goadsby, Peter J; Ashina, Messoud; Al-Karagholi, Mohammad Al-Mahdi; Sinclair, Alexandra; Mitsikostas, Dimos; Magis, Delphine; Pozo-Rosich, Patricia; Irimia Sieira, Pablo; Làinez, Miguel JA; Gaul, Charly; Silver, Nicholas; et al.
Introduction: Non-invasive vagus nerve stimulation (nVNS; gammaCore®) has the potential to prevent migraine days in patients with migraine on the basis of mechanistic rationale and pilot clinical data. Methods: This multicentre study included a 4-week run-in period, a 12-week double-blind period of randomised treatment with nVNS or sham, and a 24-week open-label period of nVNS. Patients were to administer two 120-second stimulations bilaterally to the neck three times daily (6–8 hours apart). Results: Of 477 enrolled patients, 332 comprised the intent-to-treat (ITT) population. Mean reductions in migraine days per month (primary outcome) were 2.26 for nVNS (n = 165; baseline, 7.9 days) and 1.80 for sham (n = 167; baseline, 8.1 days) ( p = 0.15). Results were similar across other outcomes. Upon observation of suboptimal adherence rates, post hoc analysis of patients with ≥ 67% adherence per month demonstrated significant differences between nVNS (n = 138) and sham (n = 140) for outcomes including reduction in migraine days (2.27 vs. 1.53; p = 0.043); therapeutic gains were greater in patients with aura than in those without aura. Most nVNS device-related adverse events were mild and transient, with application site discomfort being the most common. Conclusions: Preventive nVNS treatment in episodic migraine was not superior to sham stimulation in the ITT population. The "sham" device inadvertently provided a level of active vagus nerve stimulation. Post hoc analysis showed significant effects of nVNS in treatment-adherent patients. Study identification and registration: PREMIUM; NCT02378844;https://clinicaltrials.gov/ct2/show/NCT02378844